Pharmacokinetics and Pharmacodynamics of a Novel Virulent Klebsiella Phage Kp_Pokalde_002 in a Mouse Model - Dhungana, Gunaraj; Nepal, Roshan; Regmi, Madhav; Malla, Rajani (Frontiers in Cellular and Infection Microbiology, 2021)
Phage therapy is one of the most promising alternatives to antibiotics as we face global antibiotic resistance crisis. However, the pharmacokinetics (PK) and pharmacodynamics (PD) of phage therapy are largely unknown. In the present study, we aimed to evaluate the PK/PD of a locally isolated virulent novel øKp_Pokalde_002 (Podoviridae, C1 morphotype) that infects carbapenem-resistant Klebsiella pneumoniae (Kp56) using oral and intraperitoneal (IP) route in a mouse model. The result showed that the øKp_Pokalde_002 rapidly distributed into the systemic circulation within an hour via both oral and IP routes. A higher concentration of phage in plasma was found after 4 h (2.3 x 105 PFU/ml) and 8 h (7.3 x 104 PFU/ml) of administration through IP and oral route, respectively. The phage titer significantly decreased in the blood and other tissues, liver, kidneys, and spleen after 24 h and completely cleared after 72 h of administration. In the Kp56 infection model, the bacterial count significantly decreased in the blood and other organs by 4–7 log10 CFU/ml after 24 h of øKp_Pokalde_002 administration. Elimination half-life of øKp_Pokalde_002 was relatively shorter in the presence of host-bacteria Kp56 compared to phage only, suggesting rapid clearance of phage in the presence of susceptible host. Further, administration of the øKp_Pokalde_002 alone in healthy mice (via IP or oral) did not stimulate pro-inflammatory cytokines (TNF-α and IL-6). Also, treatment with øKp_Pokalde_002 resulted in a significant reduction of pro-inflammatory cytokines (TNF-α and IL-6) caused by bacterial infection, thereby reducing the tissue inflammation. In conclusion, the øKp_Pokalde_002 possess good PK/PD properties and can be considered as a potent therapeutic candidate for future phage therapy in carbapenem-resistant K. pneumoniae infections.